HEMATOLOGICAL PARAMETERS IN THE TREATMENT OF ENDOMETRITIS IN COWS - Hakim Niyazov; Salokhiddin Abdiev; Saltanat Khudoyarova; Mahbuba Quyliyeva (American Journal of Biodiversity, 2025)
In the treatment of acute purulent-catarrhal endometritis in pedigree cows after calving, an emulsion consisting of 10 g of oxytetracycline, 4 ml of ASD, 6 ml of tannin, 50 ml of fish oil, and 30 ml of distilled water was administered intrauterinely. Additionally, 20 ml of Penstrip-400 was injected intramuscularly. This method proved to be one of the most effective and convenient approaches for treating postpartum acute purulent-catarrhal endometritis.